Estudo farmacológico de extratos, frações e substâncias isoladas de plantas medicinais e do pólen e geoprópolis de Melipona subnitida Ducke - Dias, Thays de Lima Matos Freire (2015)
In this study, we identified the antinociceptive and anti-inflammatory effects of the flavonoids PMT1 and PMT2 from Piper montealegreanum, geopropolis and pollen from stingless bee Melipona subnitida and the phenolic fractions extraction, such as the ethanolic extract, fractions and a catechin (XACC-1) isolated from Ximenia americana. The antinociceptive effects of PMT1 and PMT2 (0.1, 1, 30 and 100 μmol/kg, i.p.) were evaluated using the classical tests acetic acid-induced writhing, reduced the writhings with an ID50 of 0.58 and 0.44 μmol/kg, respectively. Moreover, these flavonoids (100 μmol/kg, i.p.) inhibited paw-licking time in the first phase of the formalin test, but only PMT2 was active in the second phase. However, PMT1 and PMT2 (100μmol/kg, i.p.) did not increase the latency time of the animals in the hot plate. In order to evaluate the anti-inflammatory effect of these flavonoids, capsaicin-induced ear oedema assay was carried out. Both flavonoids (100μmol/kg, i.p.) were active in this model. The ethanolic extract of pollen colleted by M. subnitida, the fractions ethyl acetate and hydromethanol and the flavonoid tricetin, when tested in mice, induced antinociceptive effects. The anti-inflammatory activity of the flavonoid tricetin was also confimed. Moreover, acetic acid-induced writhing test was initially used to evaluate the antinociceptive activity of the ethanolic extracts (100 mg/kg) of geopropolis and their phenolics fractions (100 mg/kg). The results demonstrate that the ethanolic extract (100 mg/kg), produced inhibition of abdominal constrictions induced by acetic acid in mice (p<0.05), with inhibitions of 96.9% to 100%. Phenolic fractions at the same concentration also inhibited the number of writhes (p<0.05) from 71.4% to 93.5%. The fact that the ethanolic extracts showed slightly greater antinociceptive activities than the phenolic fractions suggests that geopropolis contains other compounds responsible for this activity and should be chemically investigated, however the phenolic fraction is probably principally responsible for this activity. The antinociceptive and anti-inflammatory action of the ethanolic extract, fractions and XACC-1 isolated from X. americana were also determined utilizing in vivo models such as acetic acid-induced writhing, the formalin test, hot plate test, Zymosan A-induced peritonitis and an in vitro cyclooxygenase inhibition assay. The writhing test revealed antinociceptive effects of all samples from X. americana. In the formalin test verified an antinociceptive effect in both the early and late phases by XACC-1, while the chloroform fraction showed a lower antinociceptive effect in the first phase; and the aqueous fraction and ethanolic extract of stem bark caused significant inhibition in the second phase. XACC-1 and the ethyl acetate fraction had no central antinociceptive effect in the hot plate test. Anti-inflammatory effects were determined for Zymosan A-induced peritoneal inflammation and the data indicated that XACC-1, the hydromethanol fraction, the ethanolic extract and the ethyl acetate fraction reduced the number of recruited cells. Moreover, it observed that XACC-1 also inhibited in vitro COX-1 and COX-2. The biological actions showed in the present study demonstrate that PMT1 and PMT2 from P.montealegreanum, tricetin, extract and factions from pollen and extract and fractions geopropolis both from M. subnitida, such as the extract, fractions and XACC-1 from X. americana produce antinociceptive and anti-inflammatory responses.